A STUDY OF COMMUNITY CULTURAL ELEMENTS ON MIANGAS ISLAND, INDONESIA - Yuwono, Ardi Tri; Vicaldo, Vengadcruz (Kusa Lawa, 2025)
Culture can be understood as the whole of human behavior in life obtained through the learning process. There are seven cultural elements, namely: (1) language; (2) knowledge system; (3) social organization system (community); (4) equipment and technology systems; (5) economic and livelihood systems; (6) the religious system, as well as; (7) art. These seven elements can be found in the Miangas Island community, which is strategically located on the sea border and makes it a meeting point for various cultures and receives influence from the Philippines. This research aims to explore the seven cultural elements that exist on Miangas Island. The method used in this study is a cultural research method with a qualitative approach. In terms of equipment and living supplies, the people of Miangas Island rely on the manufacture of wooden boats and fishing gear. Their main livelihood is as fishermen and farmers. In terms of social structure, the people of Miangas Island in the past had a traditional leadership system consisting of kapitelaut, ratumbanua, and inanghuwanua. Commonly spoken languages on the island include Indonesian, Talaud, Tagalog, and several other languages. The arts that developed on Miangas Island were the M?tagonggong Arts and the M?bawalas? Arts. The knowledge system of the people of Miangas Island is based on a calendar that calculates the phases of the moon and 17 cardinal directions. In addition, the belief system on Miangas Island includes Christianity, Catholicism, and Islam.